The last European war : September 1939/December 1941 - Lukacs, John, 1924- (London : Routledge & Kehan Paul, 2001)
"This absorbing study of the first - and decisive - phase of World War II tells not only how events happened but why they happened as they did. Eminent historian John Lukacs presents an extraordinary narrative of these two years, followed by a detailed sequential analysis of the lives of the peoples and then of the political, military, and intellectual relations and events."--BOOK JACKET.
I. The Main Events -- I. Introduction: Germany and Europe -- II. Hitler's year -- III. The coming of the war in 1939 -- IV. Reluctant war -- V. Germany triumphant -- VI. Germany governant -- VII. Germany conquerant -- VIII. Germany rampant -- IX. Germany halted -- X. A second world war -- II. The Main Movements -- I. The lives of the peoples -- II. The march of the armies -- III. The movements of politics -- IV. The relations of states -- V. The sentiments of nations -- VI. The convergences of thought and of belief.
"Cloth edition published 1976 by Anchor Press/Doubleday"--T.p. verso.
Includes bibliographical references and index.
Includes bibliographical references (p. 539-551) and index.
Keywords: Europe. -- History; World War, 1939-1945.; Europe -- History -- 1918-1945.